2007
DOI: 10.1016/j.colsurfa.2006.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation of humic acid: The performance of preformed and non-preformed Al species

Abstract: Inorganic polymeric Al coagulants have been being widely used in water treatment due to their advantages of applicability within broad pH and temperature ranges, high capacity of charge neutralization as well as less alkalinity consumption. However, the removal of dissolved organic matter (DOM) by such kind of coagulants has not been well understood because of the complexity of natural organic matter and the diversity of such polymeric Al coagulants. In this paper, coagulants with different Al speciation chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
42
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 22 publications
8
42
0
1
Order By: Relevance
“…An Al 13 species with the formula Al 13 O 14 ðOHÞ 24 ðH 2 OÞ 7þ 12 (abbreviated as Al 7þ 13 or often as Al 13 ) has been shown to be the dominant polymeric species in PACl Wang et al, 2008). These preformed polymerised Al species have the advantages of being more effective under a variety of water quality conditions compared to monomeric Al 3þ species in alum, especially at lower temperatures and a broader pH ranges (Shi et al, 2007). Although the prehydrolysed polymer coagulants have been reported to have advantages over conventional coagulants, a number of studies found that in certain conditions the coagulation efficiency of preformed Al species (Al 13 ) is not better than that of the conventional Al salt (Hu et al, 2006;Shi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An Al 13 species with the formula Al 13 O 14 ðOHÞ 24 ðH 2 OÞ 7þ 12 (abbreviated as Al 7þ 13 or often as Al 13 ) has been shown to be the dominant polymeric species in PACl Wang et al, 2008). These preformed polymerised Al species have the advantages of being more effective under a variety of water quality conditions compared to monomeric Al 3þ species in alum, especially at lower temperatures and a broader pH ranges (Shi et al, 2007). Although the prehydrolysed polymer coagulants have been reported to have advantages over conventional coagulants, a number of studies found that in certain conditions the coagulation efficiency of preformed Al species (Al 13 ) is not better than that of the conventional Al salt (Hu et al, 2006;Shi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These preformed polymerised Al species have the advantages of being more effective under a variety of water quality conditions compared to monomeric Al 3þ species in alum, especially at lower temperatures and a broader pH ranges (Shi et al, 2007). Although the prehydrolysed polymer coagulants have been reported to have advantages over conventional coagulants, a number of studies found that in certain conditions the coagulation efficiency of preformed Al species (Al 13 ) is not better than that of the conventional Al salt (Hu et al, 2006;Shi et al, 2007). More recently, research interest has been directed towards improving the coagulation and flocculation efficiency of pre-polymerised metal coagulants by incorporating polyelectrolytes or silica into their formulation (Ahmad et al, 2008;Zouboulis and Tzoupanos, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, flocs formed by Al c were found to be larger than those by other species, which is favor of the settling efficiency. Comparatively, most researchers claimed that prehydrolyzed Al b with high positive charge shows applicability within broad pH and could destabilize particles more efficiently [8,9]. It has been proven that hydrophobic and high molar mass fractions of NOMs can be efficiently removed by enhanced coagulation (EC) [10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the charge neutralization precipitates formed during the coagulation process, the adsorption on amorphous metal hydroxide precipitates contributes the HA removal [20][21][22]. Generally, charge neutralization occurs at low pH values only soluble species are present, while adsorption means the appearance of bulk hydroxide precipitation at high pH values or at high coagulant doses.…”
Section: Comparison Of Ha Removal Between Coagulation and Adsorption mentioning
confidence: 99%